2015
DOI: 10.1080/09585192.2015.1041759
|View full text |Cite
|
Sign up to set email alerts
|

Developing cultural intelligence: assessing the effect of the Ecotonos cultural simulation game for international business students

Abstract: In this study, we test the strength of a cross-cultural simulation game, Ecotonos, in the development of cultural intelligence (CQ) and self-efficacy amongst business students. Cross-cultural training is perceived as an important tool to help develop cross-cultural competence in international managers. Within the training literature, a distinction is made between various types of training, roughly the more cognitive knowledgetransferring training formats and more behavioral training formats such as cultural si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 63 publications
0
48
0
5
Order By: Relevance
“…However, the aforementioned studies also agreed that not all of the four dimensions of CQ can increase equally, and sometimes the instruction did not affect cross-cultural communication effectiveness (Bücker & Korzilius, 2015). Fisher's (2011) study even revealed that after CQ training, students' cognitive and meta-cognitive CQ decreased due to the fact that their awareness of the challenges of cross-cultural interactions was enhanced following the intervention.…”
Section: Cultural Intelligence (Cq) and Developing Cultural Competencementioning
confidence: 99%
See 1 more Smart Citation
“…However, the aforementioned studies also agreed that not all of the four dimensions of CQ can increase equally, and sometimes the instruction did not affect cross-cultural communication effectiveness (Bücker & Korzilius, 2015). Fisher's (2011) study even revealed that after CQ training, students' cognitive and meta-cognitive CQ decreased due to the fact that their awareness of the challenges of cross-cultural interactions was enhanced following the intervention.…”
Section: Cultural Intelligence (Cq) and Developing Cultural Competencementioning
confidence: 99%
“…Regarding offering cultural instruction to prepare students (including undergraduates and postgraduates) to function effectively in multicultural encounters, a number of empirical studies have evidenced that the experimental group taught with cross-cultural knowledge in a course or in a simulation mode showed an overall increased CQ performance compared with the control group without the same provision (e.g. Buchtel, 2014;Bücker & Korzilius, 2015;Eisenberg, Lee, Brück, Brenner, Claes, Mironski, & Bell, 2013;Engle & Crowne, 2014;Erez, Lisak, Harush, Glikson, Nouri, & Shokef, 2013).…”
Section: Cultural Intelligence (Cq) and Developing Cultural Competencementioning
confidence: 99%
“…Training approaches differ, ranging from passive methods, such as lectures (Buchtel, 2014), to experiential and involved methods, such as role-plays and behavior modification training (Bücker & Korzilius, 2015;Fischer, 2011). Lectures are considered cost-effective, nonthreatening, and able to transmit large amounts of information rapidly (Fischer, 2011), while experiential methods, such as simulation games, provide safe environments "for trying out new behaviors, for understanding old behaviors, and testing how other people react to what we do" (Bücker & Korzilius, 2015, p. 2000. Some studies also provided various training projects that enabled participants to interact with people from different cultures.…”
Section: Development Of Cultural Intelligencementioning
confidence: 99%
“…Experiential training seems to be most effective for the development of motivational CQ (Taras et al, 2013) and behavioral CQ (Ko et al, 2015). Classroom training, including lectures and role-plays, as well as simulation games, appears to be most important for the development of metacognitive CQ (Buchtel, 2014;Bücker & Korzilius, 2015;Eisenberg et al, 2013) and cognitive CQ (Eisenberg et al, 2013;Rehg, Gundlach, & Grigorian, 2012).…”
Section: Development Of Cultural Intelligencementioning
confidence: 99%
“…We support a stronger use of experimental designs, for instance, in the forms of simulation games (Bücker and Korzilius, 2015), randomly assigned groups, intervention groups or stimuli groups, quasi-experiments (Bogilovic et al, 2017) and field experiments. This can help to simulate effects that aid understanding the underlying processes in the association between antecedents and outcomes of CG, GM, and CC in various themes (e.g., learning, communication, teamwork).…”
Section: Be Like Victor Frankenstein: Experiments and Scrutinise Usingmentioning
confidence: 63%